2006
DOI: 10.1590/s1516-31802006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prone position on the oxygenation of patients with acute respiratory distress syndrome

Abstract: CONTEXT AND OBJECTIVE: Acute respiratory distress syndrome (ARDS) is characterized by arterial hypoxemia, and prone position (PP) is one possible management strategy. The objective here was to evaluate the effects of PP on oxygenation. DESIGN AND SETTING: Non-randomized, open, prospective, controlled clinical trial, in a surgical intensive care unit at a tertiary university hospital. METHODS: Forty-one ARDS patients underwent PP for three-hour periods. Arterial partial oxygen pressure (PaO2) was measured immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
4
0
3
Order By: Relevance
“…Only a few studies evaluated the persistent improvement in oxygenation after PrP, i.e. in the supine position as we did (22, 30, 31). The increase in oxygenation in our study was comparable to results of a meta-analysis in patients without ECMO (32).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies evaluated the persistent improvement in oxygenation after PrP, i.e. in the supine position as we did (22, 30, 31). The increase in oxygenation in our study was comparable to results of a meta-analysis in patients without ECMO (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, only Johannigman et al (2000) reported the use of a specialist proning device (Vollman Prone Positioner; Hill‐ROM, Batesville, IN, USA), and none of the studies documented the use of cushions. Hering et al (2001) and Rossetti et al (2006) did report that no cushions or measures were taken to alleviate positional restrictions of the abdomen. This means that ICU nurses do not have clear guidance as to how best to achieve a ‘free abdomen’ in patients who they position prone.…”
Section: Discussion and Implications For Nursing Practicementioning
confidence: 99%
“…A non‐randomized trial by Rossetti et al (2006) demonstrated a significant correlation between patients' body weight and response to the prone position, with a trend towards those who were heavier responding better. This finding would support the understanding that in the supine position the organs of the abdominal cavity restrict the movement of the diaphragm, thereby reducing residual capacity and closure of the alveoli in dependent zones (Marik, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Rossetti et al (33) investigated the effect of three hours ventilation in prone position on arterial oxygenation in ARDS patients. Forty one patients with diagnosis criteria for ARDS where included in this trial.…”
Section: Prone Positionmentioning
confidence: 99%